1993
DOI: 10.1021/jm00062a005
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships of 8-styrylxanthines as A2-selective adenosine antagonists

Abstract: A series of substituted 8-styryl derivatives of 1,3,7-alkylxanthines was synthesized as potential A2-selective adenosine receptor antagonists, and the potency at rat brain A1- and A2-receptors was studied in radioligand binding experiments. At the xanthine 7-position, only small hydrophobic substituents were tolerated in receptor binding. 7-Methyl analogues were roughly 1 order of magnitude more selective for A2 versus A1 receptors than the corresponding 7-H analogues. 1,3-Dimethylxanthine derivatives tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 13 publications
1
116
2
Order By: Relevance
“…103 Of particular importance was the discovery that substitution at C-8 with a styryl functional group yielded potent and selective A 2A antagonists. 24,46,102,103 Therefore, a large portion of the of reported A 2A antagonists are 1,3-dimethyl, 1,3-diethyl or 1,3-dipropyl substituted xanthinyl analogues bearing an (E)-8-styryl moiety modified on the phenyl ring.…”
Section: Methylxanthines As a 2a Antagonistsmentioning
confidence: 99%
See 3 more Smart Citations
“…103 Of particular importance was the discovery that substitution at C-8 with a styryl functional group yielded potent and selective A 2A antagonists. 24,46,102,103 Therefore, a large portion of the of reported A 2A antagonists are 1,3-dimethyl, 1,3-diethyl or 1,3-dipropyl substituted xanthinyl analogues bearing an (E)-8-styryl moiety modified on the phenyl ring.…”
Section: Methylxanthines As a 2a Antagonistsmentioning
confidence: 99%
“…106 Another xanthinyl derivative, CSC is commercially available and is used extensively as a reference A 2A antagonist in pharmacological studies. 24,25 Replacement of the styryl phenyl ring with a heterocyclic system as in the case of (E)-1,3-dipropyl-7-methyl-8-[2-(3-thienyl)ethenyl)]xanthine (DPMTX) (5) also produces a series of potent and selective A 2A antagonists. 107 Structure-activity relationship studies have shown that alkylation at N-7 of the xanthine and the trans geometry about the styryl double bond are structural features that are important for potent A 2A antagonism (Table 3).…”
Section: Methylxanthines As a 2a Antagonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…An isothiocyanate derivative (1,3,7-trimethyl-8-(3-isothiocyanato-styryl)xanthine, ISC, 2) in the A 2 -selective, 8-styrylxanthine series of adenosine antagonists [Shimada et al, 1992;Jacobson et al, 1993] was prepared as a potential receptor affinity label. It was synthesized by reaction of the corresponding 3-amino derivative , 1, with thiophosgene ( Fig.…”
Section: Resultsmentioning
confidence: 99%